The Importance of Authentication and Encryption in Cloud Computing Framework Security - Brandão, Pedro (2018)
The issues of cybersecurity these days are extremely relevant. With the massive use of the Cloud Computing system, new concerns about the processes to provide this technology with security appeared. The Cloud Computing infrastructure is based on virtualization and distributed computing, often using the shared resource pooling system. For these scenarios, key issues are considered: authentication, and access control. These issues make relevant the following items: data security, regulatory data, privileged access and data recovery. The issue of security in cloud computing involves encryption, it is important to specify the advantages and disadvantages of symmetric encryption and asymmetric encryption. Parallel to this it is important to develop a set of policies for the creation of passwords and subsequent maintenance and alteration of them, as well as their security. the two mandatory pillars for security in Cloud Computing are encryption and a strong passwords policy.